Static stability in games. Part 2: Asymmetric games - Igal Milchtaich (Bar-Ilan University, Department of Economics, 2017)
Static stability in strategic games differs from dynamic stability in only considering the players' incentives to change their strategies. It does not rely on any assumptions about the players' reactions to these incentives and it is thus not linked with any particular dynamics. This paper introduces a general notion of (local) static stability of strategy profiles that is applicable to any N-player strategic game. It examines a number of important classes of games, with strategy spaces or payoff functions that have special structures, where this general notion takes a simple, concrete form. The paper explores the relations between these special cases of static stability and different versions of dynamic stability, and connects static stability in general, asymmetric games with the related, but essentially weaker, notion of static stability of strategies in symmetric games.
Keywords: C72; 330; Static stability; stability of equilibrium